Identity and Piety: Critical Discourse Analysis on Indonesian Ulema Council’s Fatwa about The Law Using Non-Moslim Religious Attributes - Subuki, Makyun; Akmal, Hilmi; Hudaa, Syihaabul (Universitas Islam Negeri Jakarta, 2023)
In December 2016, shortly after the Action to Defend Islam 212 was held, the Indonesian Ulema Council published a fatwa on the Law Using Non-Muslim Religious Attributes. This fatwa reaped controversy because it was followed by sweeping action by a number of mass organizations against the Christmas attribute. Since this fatwa caused controversy, this study sought to examine it with a critical discourse analysis approach. This study covers three dimensions of the fatwa: the textual dimension, the dimension of discursive practice, and the dimensions of social practice. Based on the analysis that has been carried out, this study has three findings. First, linguistic analysis of this fatwa showed that the fatwa is an ideological text. Furthermore, this fatwa has intertextuality with other texts, namely the opinions of previous ulemas, which also prohibit the use of religious attributes of non-Muslims. Second, as a discursive practice, this fatwa affirms the view of several religious mass organizations that not only forbid wearing religious attributes of non-Muslims but also at the same time justified their attitude in sweeping against the religious attributes of non-Muslims, for example, Islamic Front Defense (FPI) and Klaten Islamic Paramilitaries (LAKIK). Third, situationally and institutionally, this fatwa is possible to be issued not only because of the encouragement of several mass organizations that consider that using religious attributes of non-Muslims is haram but also because of the influence of consolidation of these mass organizations, which rich their peak level after the series of Action to Defend Islam. Lastly, a value system that views identity as permanent and unchanging in Indonesian Muslim society is still very dominant, so it is also determining the issuance of this fatwa. Pada bulan Desember 2016, tak lama setelah Aksi Bela Islam 212 digelar, Majelis Ulama Indonesia menerbitkan fatwa tentang Hukum Penggunaan Atribut Keagamaan Non-Muslim. Fatwa ini menuai kontroversi karena disusul aksi sapu bersih sejumlah ormas yang menentang atribut Natal. Karena fatwa ini menimbulkan kontroversi, maka penelitian ini berupaya mengkajinya dengan pendekatan analisis wacana kritis. Kajian ini mencakup tiga dimensi fatwa: dimensi tekstual, dimensi praktik kewacanaan, dan dimensi praktik sosial. Berdasarkan analisis yang telah dilakukan, penelitian ini mempunyai tiga temuan. Pertama, analisis kebahasaan fatwa ini menunjukkan bahwa fatwa tersebut merupakan teks ideologis. Lebih lanjut, fatwa ini memiliki intertekstualitas dengan nash lain, yaitu pendapat para ulama terdahulu yang juga melarang penggunaan atribut agama non-Muslim. Kedua, sebagai praktik diskursif, fatwa ini mengafirmasi pandangan beberapa ormas keagamaan yang tidak hanya melarang pemakaian atribut keagamaan non-Muslim namun sekaligus mem sikapnya dalam melakukan penyisiran terhadap atribut keagamaan non-Muslim, mislanya Front Pembela Islam (FPI) dan Laskar Islam Klaten (LAKIK). Ketiga, secara situasional dan institusional, fatwa ini dimungkinkan dikeluarkan bukan hanya karena dorongan dari beberapa ormas yang menganggap penggunaan atribut keagamaan non-Muslim haram, namun juga karena pengaruh konsolidasi ormas-ormas tersebut, yang besar di mana puncaknya setelah rangkaian Aksi Bela Islam. Terakhir, sistem nilai yang memandang identitas sebagai sesuatu yang permanen dan tidak berubah dalam masyarakat Islam Indonesia masih sangat dominan sehingga ikut menentukan dikeluarkannya fatwa ini.